Research On Hydronyms and Their Importance - Axmedova Umidaxon Yodgorjon qizi; Axmedova Mashhuraxon Ulug‘bek qizi (Genius Publishing Group, 2021)
This article provides information on the importance of hydronyms and their structural features. The urgency is to overcome such problems as the misinterpretation of names as a result of not fully understanding the meaning of historical names today. The purpose is to study the water bodies of our country, to increase their historical significance, as well as to develop the historical consciousness of the people. The article provides explanations using the research conducted by our scientists, their scientific conclusions. As an example, data on the etymology of the Amudarya, Syrdarya, Kashkadarya and Zarafshan rivers flowing through the country were used. In short, hydronyms, and toponyms in general, are a mirror of our history. It is our responsibility to understand, analyze and disseminate information about them to the public.
Keywords: Hydronyms; Toponyms; Oikonyms; River